'I didn't know what was in front of me'—Bereaved parents' experience of adapting to life when a co‐parent of dependent children has died with cancer. Issue 10 (5th September 2022) - Hanna, Jeffrey R.; Semple, Cherith J.
Abstract: Objective: It is not clear how the bereaved parent navigates life with the children after a co‐parent has died. The objective of this study is to explore bereaved parents' experience of managing life when a co‐parent of dependent children has died with cancer. Methods: Twenty‐one in‐depth interviews were conducted with bereaved parents when a co‐parent died with cancer. Data were analysed thematically. Results: Bereaved parents highlighted how their children was their key focus after the death of a co‐parent with cancer, as they effortfully strived to be a 'perfect parent'. While some bereaved parents struggled to adapt to the role as a sole parent, others described the importance of maximising social networks to help with the practical aspects of parenting. However, most bereaved parents described intense feelings of loneliness as they navigated parenting alone. To help navigate this post‐bereavement period, parents considered it important for their children to openly talk about the deceased parent. Also, meeting others who have experienced similar situations was helpful for the bereaved parent and children, providing hope for the future. Results are discussed under two themes: (1) adapting to life without the parent, and (2) a desire to keep the memory alive of the parent that died with cancer. Conclusions: Bereaved parents should be encouraged to practice self‐care when a co‐parent has died from cancer so they can appropriately meet the needs of their children. Bereaved parents should be reassured that showing emotion in front of the children is helpful and could facilitate better grief experiences for the whole family.